Le Quaternaire des cantons de Guigues, Baby, Duhamel et Laverlochere, comte de Témiscamingue, Québec - Vincent, Jean-Serge (University of Ottawa (Canada), 1971)
Abstract not available.
Keywords: History, Canadian.